Preparation of Lignin Nanoparticles from Wood Waste for Wood Surface Treatment - Florian Zikeli; Vittorio Vinciguerra; Alessandro D’Annibale; Donatella Capitani; Manuela Romagnoli; Giuseppe Scarascia Mugnozza (Nanomaterials, 2019)
Lignin was isolated from wood wastes comprising Iroko sawdust (IR) and mixed sawdust from Iroko and Norway spruce (IRNS), furnished by a local wood houses producer. The respective acidolysis lignin fractions were structurally characterized using pyrolysis (Py)-GCMS, two-dimensional heteronuclear single quantum correlation nuclear magnetic resonance (2D HSQC NMR), Fourier-transform infrared FTIR and ultraviolet-visible (UV-VIS) spectroscopies, size exclusion chromatography, and standard wet-chemistry methods for Klason lignin and polysaccharides determination. The isolated lignin fractions were subsequently used for the preparation of lignin nanoparticles (LNPs) using a non-solvent method. LNPs were then used for wood surface treatment using a dip-coating technique. The coated wood samples were analyzed by colorimetry and scanning electron microscopy (SEM) before and after artificial weathering experiments in a UV chamber to investigate the UV protection potential of the LNPs coatings. Wood samples dip-coated with LNPs showed promising surface modifications resembling a sort of film of fused LNPs. Coatings made from IR-LNPs and IRNS-LNPs performed significantly better in artificial weathering experiments than uncoated reference samples.